The Impact of Green Tea Consumption and Its Extracts on Fat Reduction and Weight Loss - Anita Ptak; Michał Szyc (Quality in Sport)
Introduction: Obesity and overweight are major health problems and challenges in the world today. It is the task of modern pharmacology, medicine and dietetics to search for new therapeutic methods to reduce body weight and body fat. Green tea has been a focus of research on its effects on weight reduction for many years. This article will analyse the available studies on the effectiveness of green tea on body weight and body fat reduction in obese and overweight people. Aim of the study: The aim of this review is to analyse the available literature in order to answer the question of whether green tea and green tea extracts (GTE) have an effect on weight loss, body fat reduction and associated metabolic processes. Materials and method: For a comprehensive review on the effects of green tea on weight and body fat reduction, we reviewed studies and literature available in databases such as PubMed and Google Scholar by searching through keywords such as ‘green tea’, ‘obesity’, ‘fat’, ‘weight loss’, ‘matcha’. Conclusion: green tea and its isolated substances such as epigallocatechin-3-O-gallate (EGCG) appear to have a positive effect on weight and body fat reduction in obese and overweight individuals. It is likely that consumption of green tea extract increases fat oxidation during exercise. In addition, supplementation had a positive effect in a group of diabetics, polycystic ovary syndrome and metabolically stressed patients. The best effects from supplementation were obtained by those who additionally had physical activity. It is suggested that research on green tea, especially on matcha, should continue, as very little reliable research has been produced on this topic